10‐Year Associations Between Tumor Necrosis Factor Receptors 1 and 2 and Cardiovascular Events in Patients With Stable Coronary Heart Disease: A CLARICOR (Effect of Clarithromycin on Mortality and Morbidity in Patients With Ischemic Heart Disease) Trial Substudy. Issue 9 (12 September 0207) - Carlsson, Axel C.; Ruge, Toralph; Kjøller, Erik; Hilden, Jørgen; Kolmos, Hans Jørn; Sajadieh, Ahmad; Kastrup, Jens; Jensen, Gorm Boje; Larsson, Anders; Nowak, Christoph; Jakobsen, Janus Christian; Winkel, Per; et al.
Abstract : Background: We aimed to assess the associations and predictive powers between the soluble receptors for tumor necrosis factor (TNF)‐α (TNFR1 and TNFR2) and cardiovascular outcomes in patients with stable coronary heart disease. Methods and Results: CLARICOR (Effect of Clarithromycin on Mortality and Morbidity in Patients With Ischemic Heart Disease) is a randomized clinical trial comparing clarithromycin with placebo in patients with stable coronary heart disease. The primary outcome was a composite of nonfatal acute myocardial infarction, unstable angina pectoris, cerebrovascular disease, and all‐cause mortality. Patients were followed up for 10 years; discovery sample, those assigned placebo (1204 events in n=1998); and replication sample, those assigned clarithromycin (1220 events in n=1979). We used Cox regression adjusted for C‐reactive protein level, established cardiovascular risk factors, kidney function, and cardiovascular drugs. After adjustments, higher serum levels of TNFR1 and TNFR2 were associated with the composite outcome in the discovery sample (hazard ratio per SD increase, 1.13; 95% confidence interval, 1.05–1.22; P =0.001 for TNFR1; hazard ratio, 1.16; 95% confidence interval, 1.08–1.24; P <0.001 for TNFR2). The associations were similar in the replication sample. The associations with the composite outcome were mainly driven by acute myocardial infarction, cardiovascular mortality, and noncardiovascular mortality. The addition of TNFR1 and TNFR2 to established cardiovascular risk factors improved prediction only modestly (<1%). Conclusions: Increased concentrations of circulating TNFR1 and TNFR2 were associated with increased risks of cardiovascular events and mortality in patients with stable coronary heart disease. Yet, the utility of measuring TNFR1 and TNFR2 to improve risk prediction in these patients appears limited. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00121550.